2019
DOI: 10.1111/apt.15160
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the epidemiology of inflammatory bowel disease among Jewish Israeli adolescents: a population‐based study

Abstract: Background: The incidence and prevalence trends of inflammatory bowel disease (IBD) vary between developed and developing countries. Aim: To investigate the prevalence and associated sociodemographic factors of IBD in Israeli Jewish adolescents Methods: The files of the army medical corps were reviewed for adolescents recruited in 2002-2016 with confirmed IBD. Covariate data included birth date, patient and parental country of birth, number of children in the household, age at diagnosis, and socioeconomic stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 53 publications
1
12
0
1
Order By: Relevance
“…In pediatric patients (<17 years), 24 had IBD, among these 14/24 had UC. A similar frequency was found in studies reported in the literature [15,16,17]. In Romania, the trend of age diagnosis seems to be similar to studies reported in literature: CD was diagnosed at a younger age than UC.…”
Section: Discussionsupporting
confidence: 89%
“…In pediatric patients (<17 years), 24 had IBD, among these 14/24 had UC. A similar frequency was found in studies reported in the literature [15,16,17]. In Romania, the trend of age diagnosis seems to be similar to studies reported in literature: CD was diagnosed at a younger age than UC.…”
Section: Discussionsupporting
confidence: 89%
“…Inflammatory bowel disease (IBD) is a multifactorial disease characterized by chronic inflammation of the intestinal tract in genetically predisposed children and adults. IBD includes Crohn's disease (CD) and ulcerative colitis (UC), with pediatric patients currently accounting for up to 25% of newly diagnosed cases, reaching a point prevalence of 373 per 100,000 children by the age of 17 years …”
Section: Introductionmentioning
confidence: 99%
“…IBD includes Crohn's disease (CD) and ulcerative colitis (UC), with pediatric patients currently accounting for up to 25% of newly diagnosed cases, 1 reaching a point prevalence of 373 per 100,000 children by the age of 17 years. 2 Nutrition deficiencies in patients with IBD can be divided into those involving macronutrients, mainly protein intake, and micronutrients (vitamins, minerals, and trace elements). The latter can be found deficient even in the remission phase of both CD and UC.…”
Section: Introductionmentioning
confidence: 99%
“…While all the investigators of the participating centers in our study were responsible for the primary examination of new patients aged <18 years, approximately one-third of the participating centers in the EUROKIDS cohort reported that new patients aged >15 years were always referred to an adult gastroenterologist [10]. Meanwhile, a recent study from Israel analyzing data from adolescents who had undergone obligatory medical examination at 17 years to assess their eligibility for military service, revealed a diagnosis age of 14.2±3.2 years among 1,612 patients who had been previously diagnosed with CD [5], which is comparable to the results of our study (median 14.7 years).…”
Section: Disease Phenotype Of Korean Pediatric CD At Diagnosismentioning
confidence: 99%
“…Approximately 25% of patients with CD are known to present before 20 years of age [2]. Moreover, the incidence and prevalence of pediatric CD is increasing worldwide and the age of CD diagnosis is also getting younger [3][4][5]. Meanwhile, CD is well-known as a contemporary condition of industrialized societies, and newly industrialized countries in Asia are experiencing a rapid increase in incidence [6].…”
Section: Introductionmentioning
confidence: 99%